Effect of ice addition on the properties and microstructure of cemented paste backfill at early-age. (15th July 2023) - Zhu, Chao; yang, Pan; Liu, Lang; Pu, Yuanyuan; Qi, Chongchong; Chen, Qiusong; Chen, Jie
Abstract: Introducing ice slag into cemented paste backfill is one way to simultaneously meet the challenges in hot workplaces and promote tailings recycling. In this work, iced cemented paste backfill (ICPB) at early-age were investigated with a specific emphasis on the influence of ice content. A series of tests including hydration heat, real-time measurement of electrical conductivity, temperature and volume water, SEM-EDS, unconfined compressive strength (UCS), nuclear magnetic resonance, and free-free resonant column were carried out. The results show that the addition of ice slag influenced the cement hydration through the decrease of temperature and the supply of water. Hydration heat mainly focused on the supply of water and the hydration kinetics were increased with the increase of the ice-to-cement (ICR). The temperature was decreased while the electrical conductivity was increased with the increasing ICR. Compared with CPB without ice slag, the volume water content was evidently increased upon the addition of ice slag. The pore size and permeability were increased with the increase of ICR while the bound water volume, UCS and longitudinal wave velocity were decreased with the increasing ICR. SEM-EDS supported the above results from a microstructural point of view. Highlights: The ICPB is proposed to achieve underground cooling and tailings recycling. ICPB was studied using hydration heat, SEM-EDS, NMR, UCS, ER, and FFRC. The temperature, volume water content, and electrical conductivity was measured. The effect of ice slag on hydration mechanism was discussed. The influence of ice content on properties and microstructure of ICPB was studied.